Three-dimensional sonographic findings of diprosopus: a case report and literature review - Qiao Zhou; Enbo Sha; Qian Ding; Chunli Jing (BMC Pregnancy and Childbirth)
Abstract Background Diprosopus is one of the rarest anomalies. It typically manifests as bilateral alterations and often involves anomalies within the cranial structures. In this report, we present a case of a fetus with diprosopus diagnosed prenatally. Along with reviewing relevant literature on prenatal ultrasound diagnosis of diprosopus, we aim to raise awareness of its ultrasound characteristics. Case presentation We report a case of craniofacial and intracranial abnormalities detected during a 26-week ultrasound examination. Two-dimensional ultrasound (2D ultrasound) demonstrates significant increases in head circumference, widening of the interocular distance, and abnormal echo patterns in the facial structure. Three-dimensional ultrasound (3D ultrasound) revealed the presence of three eye sockets (the lateral eye sockets contained eyeballs, while the central region exhibited fusion without visible eyeballs), two noses, and two mouths, with no abnormalities observed in other areas. The ultrasound findings suggested diprosopus. Following risk counseling at the prenatal diagnosis center, the pregnant woman decided to induce labor. The newborn passed away thirty minutes after delivery. The facial features of the newborn were consistent with the 3D ultrasound imaging, and the appearance of the trunk and limbs was normal. Both CT and MRI scans confirmed the diagnosis of diprosopus. Conclusion The prenatal 2D ultrasound revealed intracranial and facial abnormalities in the fetus. 3D ultrasound imaging clearly displayed the facial duplication anomalies, highlighting the advantages of 3D ultrasound in diagnosing diprosopus. We hope to raise awareness of this rare condition and provide insights into prenatal ultrasound diagnosis through this case.